Patent foramen ovale: a novel cardiovascular risk factor in patients with sleep disordered breathing and high altitude dwellers? (Swiss Medical Weekly, 2016)
Diseases associated with chronic hypoxaemia are a leading cause of morbidity and mortality in Western countries. Epidemiological data indicate that cardiovascular diseases contribute substantially to this problem, but the underlying mechanisms are incompletely understood. Sleep disordered breathing and high altitude exposure are frequent conditions associated with hypoxaemia. Recent evidence suggests that in these conditions the concomitant presence of a patent foramen ovale plays an important pathogenic role. For example, in patients with obstructive sleep apnoea the presence of a patent foramen ovale is associated with more severe sleep disordered breathing, nocturnal oxygen desaturation, generalised endothelial dysfunction and arterial hypertension. After patent foramen ovale closure, both sleep disordered breathing and cardiovascular phenotype improve, suggesting the existence of a possible causal link. During short-term high altitude exposure, the presence of a patent foramen ovale, by aggravating altitude-induced hypoxaemia, facilitates exaggerated pulmonary hypertension. Interestingly, there is increasing evidence showing that in high-altitude dwellers a patent foramen ovale also alters the cardiovascular phenotype. In this article we will summarise recent evidence demonstrating how a patent foramen ovale alters the cardiovascular phenotype and increases cardiovascular risk in patients with sleep disordered breathing and high-altitude dwellers.